Career decision-making difficulties among socioeconomically disadvantaged students (Bidikmisi Students) - Nadhira Ivana Anshari; Fitriani Yustikasari Lubis; Puspita Adhi Kusuma Wijayanti (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2022)
This study aims to explore the career decision-making difficulties (CDMD) of Bidikmisi students, especially the factors that may cause difficulties, such as parents’ education level and students’ gender. The measuring instrument used was Career Decision-making Difficulties Questionnaire. Random cluster sampling was conducted, and there were 154 Unpad students from four selected faculties.  The CDMD data were analyzed using descriptive and differential tests. The results of the study showed that the majority of Bidikmisi students had moderate CDMD, with the highest difficulty in the Lack of Readiness category.  There was a significant difference in CDMD based on parents’ education level in which individuals with parents with secondary and college levels of education had higher CDMD. There was no significant difference between male and female students regarding CDMD. These findings highlight the importance of career guidance for Bidikmisi students to make appropriate career decisions, mainly those with parents from specific educational backgrounds